Wpływ struktury kapitałowej w inwestycji hotelarskiej na rentowność kapitałów własnych - Szymfel, Marcin (Capital Structure in Hotel Industry and its Impact on Return on Equity, 2008)
The key goal of this paper is to describe the broad subject of defining optimal structure of capitals in hotel industry. Defining optimal structure of capitals in any businesses plays an important role in achieving acceptable return on equity. Too much debt can both lead to insolvency of the venture as well as improve return on equity. The effect is measured by comparison of EBIT to assets of the company. If earning before interest and tax is higher than cost of net debt (debt minus non-interest trade payables) than we say that the debt leverages profitability of equity. The same rule applies to most of the industries however in hotel business due to less flexible balance sheet it may not be the case. In this paper I analyze two fictitious companies. In first case we use data from the Statistical Office of Poland on achieved results in hotel business in Warsaw. Static analysis is conducted and different debt scenarios are presented in order to see how debt impacts profitability of equity. With this exercise it has been proved that the company makes the highest return on equity having aprox. 70% of debt in its balance sheet. In order to assure correctness of this conclusion another company is created where for that purpose we used data collected from independent consulting companies as well as from the biggest hotel chain in the world (by number of rooms available.) Comparing achieved results of both cases it has been concluded that the hotels in Warsaw in years 2005-2006 would have achieved higher returns on equity if they had increased debt from 60% to 70% of the assets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 548-557